2020
DOI: 10.2152/jmi.67.365
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell carcinoma of the breast – A case report –

Abstract: Spindle cell carcinoma (SpCC) of the breast is quite a rare modality classified to the metaplastic carcinoma of the breast. Regarding its biological behavior and the prognosis of the patients with this rare tumor, it has been remaining controversial. We herein report an 88 year-old woman who had a huge bleeding tumor on the right breast. She was a high-aged woman with low activities of daily life, even with some suspicion of distant organ metastasis. While the tumor proved to drastically bleed due to the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Other antibodies ER, PgR and HER2 are generally negative, resembling normalised metaplastic carcinoma. As in our case, Rekhi et al [ 17 ], Nozoe et al [ 18 ], Rito et al [ 19 ] and others also found by immunohistochemical examination that FLMCa did not express estrogen receptors, progesterone receptors, and HER2 receptors, but mainly vimentin and basal cytokeratin. In addition, immunohistochemical expression of AE1/3 and CAM5.2 was also observed, and positive expression of epithelial and mesenchymal markers in these cells may be considered indicative of the "epithelial-mesenchymal" transformation observed in these tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Other antibodies ER, PgR and HER2 are generally negative, resembling normalised metaplastic carcinoma. As in our case, Rekhi et al [ 17 ], Nozoe et al [ 18 ], Rito et al [ 19 ] and others also found by immunohistochemical examination that FLMCa did not express estrogen receptors, progesterone receptors, and HER2 receptors, but mainly vimentin and basal cytokeratin. In addition, immunohistochemical expression of AE1/3 and CAM5.2 was also observed, and positive expression of epithelial and mesenchymal markers in these cells may be considered indicative of the "epithelial-mesenchymal" transformation observed in these tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, another pitfall is where the spindle cell component demonstrates loss of cohesion of the tumor cells and consequently mimics an angiosarcoma. This has been described in other body sites as pseudoangiosarcomatouscarcinoma and has also been reported in oral cavity SpCC [19]. Mitotic activity can vary, but averages more than one per high power field with a range from 0 to over 10.…”
Section: Spindle Cell Carcinomamentioning
confidence: 53%